Pembentukan Duta Pencegah Anemia Pada Remaja Putri di MTS Al-Amin Kecamatan Bukit Batu Kota Palangka Raya - Theresia, Nita; Aridamayanti, Bernadetta Germia; Putri, Fina Ratih Wira; Megaraya, Adhayana; Putri, Lutfi Sanggita; Handayani, Lulu (Progran Studi Farmasi Universitas Mandala Waluya, 2024)
Anemia is a condition caused by low hemoglobin levels in the blood. Anemia often occurs in young women who are growing and lacking iron. Therefore, efforts are needed to increase public awareness and knowledge, especially teenager, about anemia. In an effort to increase public awareness and knowledge about anemia, one of the activities that can be carried out is the selection of anemia ambassadors for teenager at junior high school level. The selection of young women's anemia ambassadors was carried out to select teenager who could be examples and motivators for their friends in preventing and overcoming anemia. The selection of anemia ambassadors for junior high school teenager was carried out using various criteria, such as criteria for knowledge about anemia, criteria for ability to speak in public, criteria for good personality, and criteria for being physically healthy. The selection of ambassadors was carried out over a period of 2 days in August 2023, attended by 18 female students from MTS Al-Amin, Bukit Batu District, Palangka Raya City. The selection of teenager's anemia ambassadors is not only based on physical appearance, but also based on their qualities and abilities. The selection of anemia ambassadors for young women at junior high school level is an effort to increase public awareness and knowledge about anemia, especially among teenager.